Draft Event Five Year Plan 1985-90 and Annual Plan 1985-86 Government of Haryana - Planning Commission (Planning Commission, 1985)
The basic development strategy of the State Government has been to accelerate the pace of development and create opportunities for all sections of the people. the main features of our economic policy have been to develop agriculture, increase farm production through a judicious mix of incentives to the farmers with an access to improved agricultural practices in a package form, to strengthen the infrastructure and the base of the economy by increasing the irrigation and power potential and providing a net work of village link roads and comprehensive road transport system, to develop cottage and small industries in the rural areas, to attract investment in medium and large scale industry through incentives and to bring improvement in health, education and other social services, to improve the living standard of the people in general and weaker sections of the society in particular and to reorient the educational and vocational programmes towards more effective development and utilisation of human resources.
Government of Haryana, Planning Department